2018
DOI: 10.1038/s41433-018-0219-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy and duration of action of dexamethasone implant, in vitrectomised and non-vitrectomised eyes with persistent diabetic macular oedema

Abstract: Purpose To evaluate the efficacy and duration of action of an intravitreal (dexamethasone (Ozurdex)) implant in vitrectomised and non-vitrectomised eyes with persistent diabetic macular oedema (DMO). Methods We retrospectively analysed the records for 18 eyes that had or had not been vitrectomised but required an intravitreal dexamethasone implant for DMO after a poor response to anti-vascular endothelial growth factor. Optical coherence tomography and visual acuity (VA) examinations were performed before and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 38 publications
(44 reference statements)
1
18
0
Order By: Relevance
“…Multiple studies have demonstrated at least equivalence in BCVA response to DEX in vitrectomized versus nonvitrectomized eyes. 28,29 These results were in eyes with DME; however, in our cohort of eyes with uveitis, a significantly better BCVA outcome was noted in the vitrectomized eyes. The majority of these vitrectomized eyes were treated with membrane peeling procedures at the time of vitrectomy for epiretinal membrane or macular hole.…”
Section: Uveitismentioning
confidence: 56%
“…Multiple studies have demonstrated at least equivalence in BCVA response to DEX in vitrectomized versus nonvitrectomized eyes. 28,29 These results were in eyes with DME; however, in our cohort of eyes with uveitis, a significantly better BCVA outcome was noted in the vitrectomized eyes. The majority of these vitrectomized eyes were treated with membrane peeling procedures at the time of vitrectomy for epiretinal membrane or macular hole.…”
Section: Uveitismentioning
confidence: 56%
“…Both groups also shared the same pharmacokinetics after intravitreal placement of dexamethasone implants. Comparable visual/anatomical outcomes and rates of postinjection ocular hypertension were noted between vitrectomized and nonvitrectomized eyes after dexamethasone implant for DME in five previous clinical studies [31][32][33][34][35][36][37]. Dexamethasone implant injections also resulted in noticeable visual gain and foveal thickness reduction in vitrectomized patients with DME.…”
Section: Discussionmentioning
confidence: 68%
“…Çevik et al 31 also reported that DEX was similarly effective in the treatment of DME in eyes with and without vitrectomy. Bastakis et al 32 reported that previous vitrectomy did not adversely affect the effectiveness of DEX in patients with refractory DME, and that the maximum effect was observed within the first 3 months in both vitrectomized and nonvitrectomized eyes.…”
Section: Discussionmentioning
confidence: 98%